Социально–экономические и правовые проблемы развития предпринимательства в условиях цифровой экономики - Гонтарева, И. (Baltic International Academy, 2019)
Широке впровадження цифрових технологій вносить зміни в структуру соціально-економічних відносин між працею і капіталом. Метою є аналіз взаємозв’язку між характеристиками цифрової економіки та можливостями розвитку підприємництва. Для досягнення мети показана необхідність взаємодоповнюваності, комплементарності, між традиційною і цифровий економіками; виділені основні – з позиції підприємництва, характеристики цифрової економіки; проведено аналіз бізнес-можливостей, що випливають з особливостей цифрової економіки. // Wide introduction of digital technologies brings in change in the structure of socio-economic relations between labour and capital. An aim is an analysis of intercommunication between descriptions of digital economy and possibilities of development of entrepreneurship. For gaining end the necessity is shown of complementaryness between traditional and digital economies; the basic are distinguished – from position of enterprise, description of digital economy; the analysis of business-possibilities following from the features of digital economy is conducted.
Keywords: доходи населення; цифрові технології; household income; entrepreneurship; digital technologies